TNFAIP3, TNIP1, and MyD88 Polymorphisms Predict Septic-Shock-Related Death in Patients Who Underwent Major Surgery - Jiménez-Sousa, Maria Ángeles (J Clin Med, 2019)
Background: In many immune-related diseases, inflammatory responses and several clinical outcomes are related to increased NF-κB activity. We aimed to evaluate whether SNPs related to the NF-κB signaling pathway are associated with higher susceptibility to infection, septic shock, and septic-shock-related death in European patients who underwent major surgery. Methods: We performed a case-control study on 184 patients with septic shock and 212 with systemic inflammatory response syndrome, and a longitudinal substudy on septic shock patients. Thirty-three SNPs within genes belonging to or regulating the NF-κB signaling pathway were genotyped by Agena Bioscience’s MassARRAY platform. Results: No significant results were found for susceptibility to infection and septic shock in the multivariate analysis after adjusting for multiple comparisons. Regarding septic-shock-related death, patients with TNFAIP3 rs6920220 AA, TNIP1 rs73272842 AA, TNIP1 rs3792783 GG, and TNIP1 rs7708392 CC genotypes had the highest risk of septic-shock-related death in the first 28 and 90 days. Also, the MyD88 rs7744 GG genotype was associated with a higher risk of death during the first 90 days. Haplotype analysis shows us that patients with the TNIP1 GAG haplotype (composed of rs73272842, rs3792783, and rs7708392) had a lower risk of death in the first 28 days and the TNIP1 AGC haplotype was associated with a higher risk of death in the first 90 days. Conclusions: The SNPs in the genes TNFAIP3, TNIP1, and MyD88 were linked to the risk of septic-shock-related death in patients who underwent major surgery.